Economy Dimension of Sustainable Development Index of Solar Powered Electricity Project in Pilolaheya And Pelita Hijau Villages of Bonebolango Regency - Ralin Hinelo (Journal of International Conference Proceedings (JICP), 2018)
Several villages in Bone Bolango Regency are isolated because of geographical conditions and conservation reasons. There are no access road from paved road which can be used by PLN to installed grid. Several programs have been launched, including supply of electricity using renewable energy such as Micro hydro electric and solar cell, to help the villagers from blackout. Unfortunately most of installed power plants did not operate continuously since the human resources in the village is too weak to handle and maintain the sophisticated electrical instrument. Story of in Bone Bolango is not unique there are many similar stories in the entire Indonesia. To address why the ideal program of government is failing, we proposed this research which has ultimate aim to solve the existing problem in the society through research using transdisciplinary approach. Our starting location is Bone Bolango regency where we have been in contact for years. The first year of research is focused on framing the problems in the society through eyes of researchers (academics), government and people. The second year of research will be focused on transferring knowledge from each side to the others with aim to create goal oriented solution. Ones we have it in the third year, we will delivered that together (co delivered) and see what happen.The output research in every year is article published in peer reviewed and Scopus indexed journals and reputable international conference in Indonesia and Southeast Asia. Keywords: Isolated, sustainable development, transdisciplinary approach.